Laparoscopic Anterior Partial Fundoplication is Comparable With Nissen Fundoplication for Gastroesophageal Reflux Disease. Issue 1 (February 2017) - Lal, Pawanindra; Shah, Swati H.; Leekha, Nitin; Puri, Amarender Singh
Abstract : Background: Laparoscopic Nissen fundoplication (LNF) has been the gold standard for gastroesophageal reflux disease (GERD), but the side effects of dysphagia and bloating have lead to interest in partial fundoplication as an alternative. Aim: To compare the symptomatic and objective parameters after LNF and laparoscopic anterior partial fundoplication (LAPF) in patients with GERD. Patients and Methods: The study was conducted in the Division of Minimal Access Surgery, Maulana Azad Medical College from June 2008 to October 2016. Patients with GERD with high score on 24-hour pH monitoring were selected for surgery (LAPF) and were compared with our historical control of 25 patients who underwent LNF. The preoperative and postoperative symptom score and objective parameters were analyzed. Results: Of 50 GERD patients, 20 patients underwent surgery (LAPF) and these were compared with 25 patients who underwent LNF. Demester score, modified Visick grade decreased from 4.12, 3.23 in LNF; 4.35, 3.35 in LAPF to 0, 1 in both groups. There was significant and similar increase in lower esophageal sphincter (LES) length, intra-abdominal LES length, LES pressure. The 24-h pH) decreased from 10.18% and 8.08% to 0.85% and 1.09% in LNF and LAPF, respectively. At 1 year and 5 years of follow-up, symptom scores, manometric analysis, and pH metry evaluation remained to be improved in both the groups. Conclusions: LAPF is as effective as LNF for GERD, with less dysphagia.